Effect of Yijinjing combined with elastic band exercise on muscle mass and function in middle-aged and elderly patients with prediabetes: A randomized controlled trial - Huang, Yunda; Han, Junhua; Gu, Qing; Cai, Yanwei; Li, Jingyuan; Wang, Shasha; Wang, Suijun; Wang, Ru; Liu, Xiangyun (Frontiers in Medicine, 2022)
Introduction: This study investigated the effect of Yijinjing combined with elastic band exercise on muscle mass and muscle function in patients with prediabetes. Methods: This study was a randomized controlled trial designed in parallel (Chinese Clinical Trial Registry: ChiCTR2000039049). Participants with prediabetes (n=47) were randomly divided into control (n=21, 63.5±4.7 years,16 females) and exercise (n=26, 62.0±5.0 years, 20 females) groups. The former maintained their original lifestyle, and the latter received Yijinjing combined with elastic band exercise five times a week for six months. All the outcome measures were assessed immediately at baseline, after three-month and six-month intervention. Results: After six-month of the exercise, the body weight, body mass index, leg fat mass, gynoid fat mass, and total body fat mass in exercise group were significantly decreased compared with those at baseline (p<0.05). Compared with those at baseline, total lean mass decreased at three and six months in both groups. The total muscle mass loss in the exercise group was always less than that in control group at all time periods, but the difference was not statistically significant. Handgrip strength, gait speed, reaction time, leg power, eye-closed and single-legged standing, and sit-and-reach were significantly improved for the exercise group at three and six months (p<0.05). Gait speed and reaction time between both groups at three and six months were significant different (p<0.05), and leg power at six months (p<0.05). Compared with baseline, the reaction time of control group at six months was significantly improved (p<0.05), and no other significant changes were observed. Compared with those at baseline, fasting plasma glucose, 2-hour post-meal plasma glucose, fasting insulin, total cholesterol, and insulin resistance index in exercise group gradually decreased, and growth hormone was gradually increased with significance at six months (p<0.05). 25-hydroxyvitamin D gradually and significantly increased in both groups at three and six months (p<0.05). But two groups’ testosterone levels weren’t significant change. Conclusion: Yijinjing combined with elastic band exercise can substantially reduce the body weight and body fat content of middle-aged and elderly patients with Prediabetes, improve muscle function and growth hormone secretion, and delay muscle mass reduction and diabetes development.